Analysis of rotating object using video tracker - Djoko Untoro Suwarno (Faculty of Science and Mathematics, Universitas Kristen Satya Wacana, 2017)
The purpose of this paper is to show the use of video tracker to analyze circular motion. Measurement of circular motion such as angular velocity and angular acceleration is not easy to do observation and measurement directly. Through the video tracker tool, the analysis of speed and rotation acceleration becomes easier. The rotating object used as a research object is a spinner fidget. The initial velocity of the rotation depends on the pull of the finger on the spinner. The duration of rotating spinner fidget depends on the inertia and attenuation that occurs. Camera position and resolution of the camera greatly determine the data on the video tracker. The standard camera capability of 30 frames per second is less capable of capturing objects that rotate with high resolution.